Analysis of The Impact of Side Barriers on Road Performance Case Study Jalan Ahmad Yani Balikpapan - Maulina Trisnawati; Sara Wibawaning Respati; Mohamad Isram M. Ain (Civil Engineering Dept, Balikpapan State Polytechnics, 2022)
Ahmad Yani road section (direction of SPBU-Rapak) is an arterial road located in Balikpapan industrial area. As a result of the construction of the Balikpapan RDMP project in the industrial area, there is an increase in the on-street parking from the project vehicles that decrease the speed of passing vehicles. This study aims to determine the performance of the Ahmad Yani road (SPBU-Rapak) due to side obstacles caused by the construction of the Balikpapan RDMP project. The research includes data collection for 6 days, 2 hours each, at 15.00-17.00 WITA. The traffic performance analysis is then calculated using the Indonesia Road Capacity Guidelines method (PKJI, 2014). The study also measures the speed reduction due to the movement of the side obstacles caused by the RDMP project vehicles. The preliminary survey shows that starting at 07.30 WITA, the side of the section is dominated by cars and buses belonging to the Balikpapan RDMP project. Therefore, this study analyzes the movement of the side obstacles instead of the side obstacles itself. The result of the study is that the section has the capacity of 1426,92 pcu/hour, and the degree of saturation at 0,82. The side movement of RDMP vehicles (entering and leaving the side of the section) reduces vehicle speed by 16%-50%. The service level of this segment is included in class D. This study suggests the project to provide adequate parking facilities to tackle the side obstacle problem.